2011
DOI: 10.1038/npp.2011.155
|View full text |Cite
|
Sign up to set email alerts
|

The Mu-Opioid Receptor and the NMDA Receptor Associate in PAG Neurons: Implications in Pain Control

Abstract: The capacity of opioids to alleviate inflammatory pain is negatively regulated by the glutamate-binding N-methyl-D-aspartate receptor (NMDAR). Increased activity of this receptor complicates the clinical use of opioids to treat persistent neuropathic pain. Immunohistochemical and ultrastructural studies have demonstrated the coexistence of both receptors within single neurons of the CNS, including those in the mesencephalic periaqueductal gray (PAG), a region that is implicated in the opioid control of nocicep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
143
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 145 publications
(147 citation statements)
references
References 61 publications
2
143
0
2
Order By: Relevance
“…A decrease in KAT II activity has indeed been associated with increased cerebral glutamate levels and thus NMDA activation (37). In addition, the increased NMDA activation could interfere with opioid receptor function (38). Anatomical studies, ultrastructural analyses, and electrophysiological data have indeed suggested interactions between opioid receptors and NMDA receptors.…”
Section: Discussionmentioning
confidence: 99%
“…A decrease in KAT II activity has indeed been associated with increased cerebral glutamate levels and thus NMDA activation (37). In addition, the increased NMDA activation could interfere with opioid receptor function (38). Anatomical studies, ultrastructural analyses, and electrophysiological data have indeed suggested interactions between opioid receptors and NMDA receptors.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, activation of N-methyl-D-aspartate (NMDA) receptors within the PAG might antagonize the effects of endogenous opioid peptides and produce hyperalgesia. 25 Interestingly, under normal conditions, there is a high degree of colocalization of NMDA receptors and MORs within the PAG. 26 Molecular interaction of both of these receptors when activated within neuronal compartments has been mapped, showing that NMDA receptor activation along with MORs contribute to morphine tolerance.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, NMDA receptor pathway has been shown to be involved in modulation of cholestasisinduced antinociception in rats (Hasanein et al 2007). According to previous researches, NMDA receptors play a key role not only in pain signal transmission in the spinal cord but also in pain perception at higher brain centers (Piovesan et al 2008;Rodriguez-Munoz et al 2012;Zhou et al 2011). Therefore, we propose possible changes in NMDA receptor system may account for, at least partly, alteration in nociception threshold in the BDL model of HE.…”
Section: Days After Bdlmentioning
confidence: 97%